Research on Structural Optimization and Excitation Control Method Using a Two-Dimensional OWPT System for Capsule Robots Based on Non-Equivalent Coils - Wenwei Li; Pingping Jiang; Zhiwu Wang; Guozheng Yan (Micromachines)
The rapid development of wireless power transfer (WPT) technology has provided new avenues for supplying continuous and stable power to capsule robots. In this article, we propose a two-dimensional omnidirectional wireless power transfer (OWPT) system, which enables power to be transmitted effectively in multiple spatial directions. This system features a three-dimensional transmitting structure with a Helmholtz coil and saddle coil pairs, combined with a one-dimensional receiving structure. This design provides sufficient internal space, accommodating patients of various body types. Based on the magnetic field calculation and finite element analysis, the saddle coil structure is optimized to enhance magnetic field uniformity; to achieve a two-dimensional rotating magnetic field, a phase difference control method for the excitation signal is developed through the analysis of circuit topology and quantitative synthesis of non-equivalent magnetic field vectors. Finally, an experimental prototype is built, and the experimental results show that the one-dimensional transmitting coil achieves a minimum received voltage stability of 94.5% across different positions. When the three-dimensional transmitting coils operate together, a two-dimensional rotating magnetic field in the plane is achieved at the origin, providing a minimum received power of 550 mW with a voltage fluctuation rate of 7.68%.